Streptococcus pneumoniae Phosphotyrosine Phosphatase CpsB and Alterations in Capsule Production Resulting from Changes in Oxygen Availability - Geno, K. Aaron (American Society for Microbiology, 2014)
Streptococcus pneumoniae produces a protective capsular polysaccharide whose production must be modulated for bacterial survival within various host niches. Capsule production is affected in part by a phosphoregulatory system comprised of CpsB, CpsC, and CpsD. Here, we found that growth of serotype 2 strain D39 under conditions of increased oxygen availability resulted in decreased capsule levels concurrent with an ∼5-fold increase in Cps2B-mediated phosphatase activity. The change in Cps2B phosphatase activity did not result from alterations in the levels of either the cps2B transcript or the Cps2B protein. Recombinant Cps2B expressed in Escherichia coli similarly exhibited increased phosphatase activity under conditions of high-oxygen growth. S. pneumoniae D39 derivatives with defined deletion or point mutations in cps2B demonstrated reduced phosphatase activity with corresponding increases in levels of Cps2D tyrosine phosphorylation. There was, however, no correlation between these phenotypes and the level of capsule production. During growth under reduced-oxygen conditions, the Cps2B protein was essential for parental levels of capsule, but phosphatase activity alone could be eliminated without an effect on capsule. Under increased-oxygen conditions, deletion of cps2B did not affect capsule levels. These results indicate that neither Cps2B phosphatase activity nor Cps2D phosphorylation levels per se are determinants of capsule levels, whereas the Cps2B protein is important for capsule production during growth under conditions of reduced but not enhanced oxygen availability. Roles for factors outside the capsule locus, possible interactions between capsule regulatory proteins, and links to other cellular processes are also suggested by the results described in this study.